A comprehensive study on Li-ion battery nail penetrations and the possible solutions. (15th March 2017) - Zhao, Rui; Liu, Jie; Gu, Junjie
Abstract: Li-ion batteries are the state-of-the-art power sources for portable electronics, electric vehicles, and aerospace applications. The safety issues regarding Li-ion batteries arouse particular attentions after several accidents reported in recent years. Among various abuse conditions, nail penetration is one of the most dangerous for Li-ion batteries due to the accumulated heat generation, which could give rise to the thermal runaway and could damage entire energy storage system. In this paper, an electrochemical-thermal coupling model is developed to study the nail penetration process of Li-ion batteries. By introducing joule heating at the nail location, the model shows good agreement with the testing results. With this verified model, a comprehensive parametric study is carried out to investigate the effects of battery capacity, internal resistance, and nail diameter on the electrochemical and thermal behaviors of Li-ion batteries during the penetration processes. Furthermore, three possible solutions to prevent the thermal runaway, which includes decreasing the state of charge, improving heat dissipation, and increasing contact resistance, are compared and discussed in detail based on a series of simulations. Highlights: A coupling model is developed to simulate Li-ion battery nail penetrations. A contact resistance – contact area curve is plotted based on experiments. Simulation results show good agreements with nail tests. The behaviors of Li-ion batteries in different penetration scenarios are studied. Possible strategies to prevent thermal runaway are investigated and discussed.